Anxiety Disorders Among Children And Adolescents Living With Hiv/Aids Attending Anti-Retroviral Clinics In Maiduguri, Nigeria - Musami, Umar Baba; Kareem, Yesiru Adeyemi; Abdulmalik , Jibril; Machina, Babagana Kundi; Yerima, Mukhtar Mohammed; Ibrahim, Abdu Wakawa (Medicor : Journal of Health Informatics and Health Policy, 2024)
The global impact of Human Immunodeficiency Virus (HIV) includes anxiety disorders, which further worsen the impact and are associated with poor medication adherence, recurrent hospitalization, and poorer outcomes. The study aimed to assess the prevalence and correlates of anxiety disorders among CALWHA attending antiretroviral clinics at the University of Maiduguri Teaching Hospital. It was a comparative cross-sectional study, adopting a random systematic sampling method. The instruments used were the socio-demographic questionnaire, clinical proforma, and the Schedule for Affective Disorders and Schizophrenia for School-Aged Children Present and Lifetime Version (K-SAD-PL). Data analysis was done using SPSS version 26. The study population comprises 83 males (51.9%) and 77 females (48.1%). The participants ranged from 6-18 years, with a mean age of 11.4 years (SD=3.15). The prevalence of anxiety disorders among CALWHA is 22.0%. The disclosure of HIV status to CALWHA was more likely to be associated with any anxiety disorder. This was even still significant statistically after adjusting for gender (OR=2.8, CI=1.1-7.1 and (OR=2.8, CI=1.1-7.1) respectively. There is a high prevalence of anxiety disorders among the CALWHA. We, therefore, recommend the need to integrate mental health services into the care of HIV and reinforce consultation liaison psychiatry among children and adolescents.